THE MEDIATING ROLE OF BUDGET RATCHETING ON OWN-SOURCE REVENUE AND REVENUE SHARING FUNDS' EFFECT ON CAPITAL EXPENDITURE - Faisal Faisal; Akmal Huda Nasution; Edy Zulfiar; Mariana Mariana; Anhar Firdaus; Rulyanti Susi Wardhani (AIBPM Publisher, 2026)
Objectives: This study aims to analyze the direct effect of Local Own-Source Revenue (PAD) and Revenue Sharing Fund (DBH) on Capital Expenditure, as well as to examine the mediating role of Budget Ratcheting in these relationships.Methodology: The research employs a quantitative approach with multiple linear regression analysis, utilizing time-series cross-sectional data from 23 regencies/cities in Aceh Province over a five-year period (2018–2022). Data were obtained from audited Local Government Financial Statements (LKPD), covering PAD, DBH, Capital Expenditure, and Budget Ratcheting variables. The analysis was conducted using SPSS version 25, with classical assumption tests applied to ensure model validity.Findings: The results show that PAD does not have a statistically significant effect on Capital Expenditure (p = 0.234), suggesting the presence of contextual influences such as governance quality and fiscal policy implementation. Conversely, DBH demonstrates a significant positive impact on Capital Expenditure (p = 0.000), consistent with prior studies emphasizing its role in enhancing local government investment capacity. Mediation analysis reveals that Budget Ratcheting strengthens the relationship between PAD and Capital Expenditure despite the initial insignificance (p = 0.015). Moreover, Budget Ratcheting mediates the relationship between DBH and Capital Expenditure with a notable negative adjustment effect (p = 0.005).Conclusion: The study highlights the critical role of revenue-sharing mechanisms and adaptive budgeting practices in supporting regional development. Strengthening fiscal management and enhancing budget flexibility are recommended strategies to maximize the effectiveness of local revenue streams in driving capital expenditures.